Analisis Perbandingan Pembentukan Portofolio Saham Optimal dengan Model Markowitz dan Indeks Tunggal - Fatahurrazak; Yuni Ayu Anggraini (Jurnal Ilmiah Akuntansi dan Finansial Indonesia, 2023)
Optimal portfolio is a portfolio where the portfolio return is higher than the risk. This study aims to find out what stocks are formed through optimal portfolios of the Banking Sector in the LQ-45 Index with the Markowitz Model and the Single Index and find out how the differences are between the Markowitz Model and the Single Index. The sampling method for this research is saturated sampling technique which all companies that are members of the Banking Sector in LQ-45 which were listed on the Indonesia Stock Exchange during the research period (February 2019 - January 2022), totaling 6 companies. The results showed that the formation of the optimal portfolio of the Markowitz Model consisted of three stocks: BBCA, BBRI, and BTPS with a portfolio expectation return rate of 1.79% and risk portfolio of 7.28%. Meanwhile, the candidates for the Single Index Model are four stocks: BBCA, BBTN, BMRI, and BTPS where the expected return of the portfolio is 1. 51% and portfolio risk level of 0.27%.